Better recognition of qualifications - (:unkn) unknown (My University, 2024)
"Which bodies apply what processes in the recognition of qualifications from other countries? How might these practices be disseminated, supported, and improved? What are the purposes and benefits of recognition to various parties? Read this paper to find out more. The paper also describes and compares recognition practices in different education sectors (vocational education, higher education), and the regulated professions; identifies the obstacles to efficient recognition; and offers recommendations to overcome these." (Author's abstract ; BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; 370; 300; EU-Bildungspolitik; Qualifikationsrahmen; Qualifikationsnachweis; Nationaler Qualifikationsrahmen; Anrechnung von Bildungsleistungen